2018
DOI: 10.1177/0163443718813486
|View full text |Cite
|
Sign up to set email alerts
|

The smartphone as a lifeline: an exploration of refugees’ use of mobile communication technologies during their flight

Abstract: Building on the results of a qualitative study with 16 male refugees (mostly from Syria) settled in the Netherlands, this article reports on an investigation that applied insights from the Uses and Gratifications (U&G) framework and refugee studies to examine the media use of refugees and to link these to the material, social and psychological needs emerging from the journey. With a focus on the smartphone, our study distinguished four significant clusters of media U&G among the sampling population: sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 31 publications
3
57
0
5
Order By: Relevance
“…Besides, the changes due to the Peer2Peer project we analysed the influence mobile communication has on different aspects of well-being. The idea was based on studies that highlight the importance of mobile use for refugees in general (Alencar, Kondova, & Ribbens, 2018) and especially on social inclusion (Díaz Andrade & Doolin, 2017) as well as on the argument that social media can be used as "adult-free" zone (Jansz et al, 2015). We found that Snapchat could explain emotional and affectionate support-but only for the Peer2Peer project group-which is in line with our assumptions (H6).…”
Section: Discussionsupporting
confidence: 83%
“…Besides, the changes due to the Peer2Peer project we analysed the influence mobile communication has on different aspects of well-being. The idea was based on studies that highlight the importance of mobile use for refugees in general (Alencar, Kondova, & Ribbens, 2018) and especially on social inclusion (Díaz Andrade & Doolin, 2017) as well as on the argument that social media can be used as "adult-free" zone (Jansz et al, 2015). We found that Snapchat could explain emotional and affectionate support-but only for the Peer2Peer project group-which is in line with our assumptions (H6).…”
Section: Discussionsupporting
confidence: 83%
“…In Zijlstra and Van Liempt's (2017) trajectory ethnographic study, it was found that information obtained through mobile mapping applications can increase the mobility of Afghan, Iranian, and Syrian refugees, as they use GPS and other technology to cross borders while relying less on the assistance of smugglers. Interviews with Syrians revealed that they had great dependence on these applications during their flight to Europe, with many refugees referring to these tools as “my best friend” or “the most essential” ones to have on your phone (Alencar, Kondova, & Ribbens, 2018).…”
Section: Mobile Media Appropriations In Refugee Journeysmentioning
confidence: 99%
“…Therefore, the location‐based affordances of the smartphone emerged as vital for refugees to progress in their journey, or in the case of an emergency situation. In the studies of Alencar et al (2018) and Zijlstra and Van Liempt (2017), for instance, refugees highlight the importance of mobile applications to check their location and to orient themselves toward their next destinations, whereas in Gillespie et al's (2018), the communicative affordances of phones assist refugees in ensuring their safety and survival through the guidance of coastguards during the perilous sea‐crossing between Izmir (Turkey) and Greece. In certain moments, however, they need to negotiate online (in)visibility depending on the borders and actors expected to be encountered.…”
Section: Mobile Media Appropriations In Refugee Journeysmentioning
confidence: 99%
See 2 more Smart Citations